Cell alignment by smectic liquid crystal elastomer coatings with nanogrooves. Issue 5 (14th February 2020) - Babakhanova, Greta; Krieger, Jess; Li, Bing‐Xiang; Turiv, Taras; Kim, Min‐Ho; Lavrentovich, Oleg D.
Abstract: Control of cells behavior through topography of substrates is an important theme in biomedical applications. Among many materials used as substrates, polymers show advantages since they can be tailored by chemical functionalization. Fabrication of polymer substrates with nano‐ and microscale topography requires processing by lithography, microprinting, etching, and so forth. In this work, we introduce a different approach based on anisotropic elastic properties of polymerized smectic A (SmA) liquid crystal elastomer (LCE). When the SmA liquid crystal coating is deposited onto a substrate with planar alignment of the molecules, it develops nanogrooves at its free surface. After photopolymerization, these nanogrooves show an excellent ability to align human dermal fibroblasts over large areas. The alignment quality is good for both bare SmA LCE substrates and for substrates coated with fibronectin. The SmA LCE nano‐topographies show a high potential for tissue engineering.